Assessment of the photoprotective and antimicrobial activity of two dermatological creams based on Mathesia and oil of Curcuma longa L. (Zingiberaceae) on Albinos - Gustave L. Nyamangombe; Blanchard M. Mayele; Helmont L. Nkasa; Joseph D. Tshidibi; Esther M. Mpiana; Fiston B. Masikini; Gracias I. Mbokolo; Blaise M. Mbembo; Jean Jacques D. Amogu; Armandine Mubwele (Orapuh, Inc., 2024)
Introduction The fragility and sensitivity of the skin in people with albinism (PWA) have necessitated extensive research across molecular genetics, dermatology, and cosmetology. These efforts aim to address the increased susceptibility of albino skin to sun damage and dermatological conditions. Purpose This study investigates the dermatological efficacy of two galenic formulations, one based on Mathesia and the other on Curcuma longa L. (Zingiberaceae) oil, assessing their antimicrobial, anti-inflammatory, and photoprotective properties for the skin of PWA. Methods Using freeze-drying techniques for Mathesia and slight modifications of Sahouli et al.'s method for extracting Curcuma longa L. oil, we developed two creams. Their macroscopic properties, pH levels, and tyrosine concentrations were analyzed. UV-visible spectrophotometry determined their sun protection factor (SPF). An antibiogram test assessed their antimicrobial activity, and a clinical test evaluated their efficacy on PWA with and without skin conditions. Results The study revealed that both creams had good texture and appropriate pH levels. However, neither cream provided sufficient photoprotection for the sensitive skin of PWA. The Mathesia-based cream demonstrated a higher antimicrobial efficacy compared to the turmeric oil-based and neutral creams. Clinical tests showed 75% of participants had very satisfactory results, with the turmeric oil-based cream showing the most significant overall efficacy. Conclusion The creams exhibited beneficial antimicrobial and anti-inflammatory properties but were inadequate for UV protection of albino skin. Future research should focus on increasing active ingredient concentrations or exploring alternative plants to enhance tyrosine content and SPF values, potentially offering better protection and therapeutic effects for PWA.